Dampak Hubungan Bilateral Indonesia dengan Jepang Sebelum dan Sesudah Indonesia-Japan Economic Partnership Agreement (IJEPA) - Rachmaniar Dwi Zulfira (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
This study aims to determine whether or not there is a difference in the volume of Indonesian exports to Japan, Indonesian imports from Japan, Indonesian foreign investment from Japan and exchange rates before and after IJEPA. This study uses secondary data obtained from the Central Statistics Agency and the Investment Coordinating Board with a period of 9 years before and after IJEPA starting in 2000 - 2017 with a paired sample t-test analysis (paired t test). The results showed that there was no significant difference between Indonesian exports to Japan before and after IJEPA and there were significant differences between Indonesian imports from Japan, Indonesian foreign investment from Japan and the exchange rate before and after IJEPA.